IDDF2020-ABS-0023 Abdominal tuberculosis: surgical management of perforated intestinal ulcers in patients with HIV/TB. (18th November 2020) - Reshetnikov, Mikhail; Plotkin, Dmitriy; Sinitsyn, Mikhail; Stepanov, Evgeniy
Abstract : Background: The growth tendencies of abdominal tuberculosis have increased more than twice between the year 2006–2016, and primarily associated, with an increase in the number of HIV-positive individuals. The most formidable and most frequent complication of tuberculosis of the abdominal cavity is perforation of specific ulcers of the intestine. Methods: Was to evaluate the results of surgical management of patients with perforated tuberculosis ulcers of the intestine against the background of late-stage of HIV infection and to develop optimal surgical tactics for this category of patients. 149 patients with perforated tuberculosis ulcers of the intestine underwent surgical treatment at the surgical department of our clinic in the period of time between the year 2006 and 2016. Results: Ulcerative lesions of intestine were detected in all cases during laparotomy, single and multiple ulcers were located in the jejunum, iliac or cecum, more often affecting the ileocecal zone. The most optimal method of surgical management of perforated ulcers of the intestine in patients with the late stages of HIV infection is performing a resection of the affected portion of the intestine with the construction of delayed anastomosis. Conclusions: A resurgence in tuberculosis during the HIV era produces a new spectrum of presentations for the surgeon. Avoidance of construction of primary anastomosis in conditions of torpid peritonitis, as well as direct visual control during laparotomy, allows timely detection and elimination of new perforations, as well as evaluation of treatment effectiveness. (Figure 1 )